Efficiency enhancement in a switched capacitor cell interleaved buck converter using GaN-FETs - Kaur, Puneet; Jaswal, Payal; Gupta, Aditi (Institute of Advanced Engineering and Science, 2024)
In this paper, a switched capacitor cell buck converter, combining two-phase interleaved operation with gallium nitride or GaN-FET technology has been presented. These technologies make it suitable for wide range of applications where efficient power conversion is essential. To validate efficacy of the proposed converter with GaN-FET, its performance is examined in relation to a similar converter that utilizes metal-oxide semiconductor field-effect transistor (MOSFET) switches. The proposed converter offers a potential advantage over the DC-DC interleaved buck converter with MOSFET switches by allowing operation at higher frequencies, resulting in a smaller inductor value. The design parameters of the inductor have also been presented. The simulation results indicate that the converter exhibits better performance than MOSFET-based converter with regards to total power losses, input and output current ripple, output voltages and subsequently achieves higher efficiency at various duty cycles and different loads. Finally, experimental verification is done to validate the simulation results.